Association between various antioxidants in normals and chronic obstructive pulmonary disease, their alteration and impact of smoking and disease on levels of antioxidants - Bhatia, Kapil; Ambade, Vivek N.; Sontakke, Alka; Basannar, Dashrath (International Journal of Research in Medical Sciences, 2019)
Background: There is total alteration of various antioxidants in response to the oxidative stress, which is one of the major patho-physiologic hallmarks in chronic obstructive pulmonary disease (COPD) development. This study aims to establish the correlation between different antioxidants in normals and COPD, study the alteration in the correlation due to COPD and smoking as well as the impact of COPD and smoking on antioxidants levels. Methods: Study comprises of 96 normals as group I and 96 COPD patients as group II. The antioxidants albumin (Alb), bilirubin (Bil), uric acid (UA) ceruloplasmin (Cp), glutathione peroxidase (GSHPx), catalase (CAT) and superoxide dismutase 3 (SOD3) were estimated. Results: Significant lower serum Alb, UA, SOD3 and increased serum Cp and GSHPx were found in Group II. Significant correlation was found between Alb and UA (r=0.24); Bil and UA (r=0.26); Alb and CAT (r=0.211) and SOD3 and CAT (r=0.318) in normals. However, these correlations were altered in COPD where Alb correlates with Bil (r=0.235); UA with CAT (r=0.203) and SOD3 with GSHPx (r=-0.27). The correlation between SOD3 and CAT remained unaltered. Similar correlation of UA with Alb and Bil was observed in nonsmoker normals and between SOD3 and CAT in smoker normals. In COPD, no correlation was seen in nonsmokers, while in smokers Alb correlates with Bil (r=0.316) and SOD3 with CAT (r=0.317). Conclusions: These alterations may have clinical ramifications in further understanding the pathogenesis of COPD and developing therapeutic approaches.